Untargeted Metabolomics Reveals Alterations in the Primary Metabolites and Potential Pathways in the Vegetative Growth of Morchella sextelata - Deng, Kejun; Lan, Xiuhua; Fang, Qing; Li, Mengke; Xie, Guangbo; Xie, Liyuan (Frontiers in Molecular Biosciences, 2021)
Morchella sextelata, one of the true morels, has recently been artificially cultivated with stable production in China. Analysis of the variations in primary metabolites during the vegetative stages of M. sextelata is critical for understanding the metabolic process. In this study, three developmental stages were categorized based on morphological and developmental changes, including the young mushroom period, marketable mature period, and physiological maturity period. Untargeted metabolomics-based mass spectrometry was used to analyze the change of metabolites during the growth stages of M. sextelata. The result showed that the metabolites’ content at the different growth stages were significantly different. The relative contents of linoleic acid, mannitol, oleamide, and betaine were higher at each growth stage. Flavor substances were significantly metabolizable during commodity maturity, while amino acids, organic acids, and lipids were significantly metabolizing at physiological maturity. Pathway analysis of the most significant changes involved Pyrimidine metabolism, Vitamin B6 metabolism, Arginine biosynthesis, Lysine biosynthesis, and Lysine degradation. The results can provide a theoretical basis for further clarifying the metabolic regulation mechanism and lay the foundation for optimizing the cultivation process of M. sextelata.